1992
DOI: 10.1210/jcem.75.2.1386373
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of growth hormone (GH) axis in Turner's syndrome using 24-hour integrated concentrations of GH, insulin-like growth factor-I, plasma GH-binding activity, GH binding to IM9 cells, and GH response to pharmacological stimulation.

Abstract: The GH axis was studied in Turner's syndrome (TS) patients. Thirty-seven prepubertal TS patients and 42 normally growing girls (NGG; 5.5-16.3 yr old), of whom 13 were prepubertal, were studied by 24-h continuous blood withdrawal and provocative tests. The 24-h integrated concentrations of GH (IC-GH), FSH (IC-FSH), and insulin-like growth factor-I (IC-IGF-I) as well as the IC-IGF-I/IC-GH ratio were determined. An increase in IC-GH with age and progression of puberty was found in NGG, but not in TS. IC-GH in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
18
1
2

Year Published

1994
1994
2005
2005

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 22 publications
2
18
1
2
Order By: Relevance
“…Ross et al (1985) observed normal GH secretory dynamics in girls with Turner's syndrome prior to 9 years of age, but significantly decreased mean 24-h GH levels, peak amplitudes and peak frequencies in girls between 9 and 20 years of age, compared with those in age-matched normal girls. Indeed, although an agerelated increase in GH pulse amplitude is observed in normal prepubertal girls, GH pulse amplitude in girls with Turner's syndrome remains the same or even declines (Massarano et al 1989, Zadik et al 1992. These results may, however, reflect age-related increases in obesity in girls with Turner's syndrome (Cianfarani et al 1994) rather than direct effects of estrogen, since GH-releasing hormone (GHRH)-induced GH secretion and obesity are inversely related in girls with Turner's syndrome (Lu et al 1991, Reiter et al 1991.…”
Section: The Prepubertal Period: Infancy and Childhoodmentioning
confidence: 99%
“…Ross et al (1985) observed normal GH secretory dynamics in girls with Turner's syndrome prior to 9 years of age, but significantly decreased mean 24-h GH levels, peak amplitudes and peak frequencies in girls between 9 and 20 years of age, compared with those in age-matched normal girls. Indeed, although an agerelated increase in GH pulse amplitude is observed in normal prepubertal girls, GH pulse amplitude in girls with Turner's syndrome remains the same or even declines (Massarano et al 1989, Zadik et al 1992. These results may, however, reflect age-related increases in obesity in girls with Turner's syndrome (Cianfarani et al 1994) rather than direct effects of estrogen, since GH-releasing hormone (GHRH)-induced GH secretion and obesity are inversely related in girls with Turner's syndrome (Lu et al 1991, Reiter et al 1991.…”
Section: The Prepubertal Period: Infancy and Childhoodmentioning
confidence: 99%
“…In fact, in these girls the GH secretory status has been found normal (6)(7)(8)(9) or impaired, mostly after the bone age of 10 y (6) or the chronologic age of 9 y (lo), when the growth delay is already manifest. In addition, the direct demonstration of an end-organ resistance to IGF-I has yet to be demonstrated, even if recent evidence supports this hypothesis (11).…”
mentioning
confidence: 99%
“…( 17) have recently suggested that girls with Turner's syndrome lack tissue sensitivity to GH or IGF-I. However.…”
Section: Discussionmentioning
confidence: 99%
“…and expression of GH-binding protein ( 15,16). Previous studies estimating GH bioactivity by radioreceptor assays suggest that GH bioactivity is similar to that in normally growing girls ( 17,18). Also.…”
mentioning
confidence: 94%
See 1 more Smart Citation